Cerebral venous thrombosis: an unexpected complication from spinal surgery - Lourenço-Costa, B (2014)
PURPOSE: To provide new insights into the pathophysiology, prevention and diagnosis of cerebral venous thrombosis (CVT) associated with iatrogenic cerebrospinal fluid (CSF) leaks and/or external CSF drainage. METHODS: Case report and literature review. RESULTS: We describe the case of a 30-year-old woman who developed a CSF fistula after lumbar spinal surgery. The treatment included rest, hydration, caffeine, and continuous lumbar CSF drainage. After closure of the fistula, the patient complained of severe orthostatic headache. Thrombosis involving the superior sagittal sinus, the right transverse sinus, the right sigmoid sinus, and the right jugular vein was diagnosed after neurological deterioration. CONCLUSION: A few reports have associated CVT with various forms of spinal meningeal injury. However, it has been rarely documented following spinal surgery complicated by accidental durotomy and/or external lumbar CSF drainage. CSF hypovolemia may precipitate CVT in patients having prothrombotic risk factors. Patients who have or had CSF leaks and/or lumbar CSF drains who present with symptoms of intracranial CSF hypotension should remain in the horizontal position to prevent CVT. In that context, the diagnosis of CVT depends on a high degree of suspicion.